A First Report on Planting Arrangements for Alfalfa as an Economic Nurse Crop During Kura Clover Establishment - Leonard M. Lauriault; Mark A. Marsalis (Agriculture)
Alfalfa (Medicago sativa) persists for several years but must be rotated to another crop before replanting. Kura clover (T. ambiguum M. Bieb) is a perennial legume that can persist indefinitely without replanting; however, establishment is slow, which limits economic returns during the process. Two studies, each with four randomized complete blocks, were planted in two consecutive years at New Mexico State University’s Rex E. Kirksey Agricultural Science Center at Tucumcari, NM, USA, as the first known assessment evaluating alfalfa as an economic nurse crop during kura clover establishment using various kura clover–alfalfa drilled and broadcast planting arrangements. Irrigation termination due to drought limited yield measurements to three years after seeding. In that time, kura clover–alfalfa mixtures generally yielded equally to monoculture alfalfa, except for alternate row planting. After 5 years, the alfalfa stand percentage remained >80%, except for the alternate row treatment (69% stand). Kura clover monocultures attained about 40% stand, and the mixtures had a <25% stand. Alfalfa may persist for more than 5 years before relinquishing dominance to kura clover in mixtures, but the alfalfa would continue to provide economic returns as kura clover continues stand development with minimal production, but develops its root system to maximize production when released from the alfalfa nurse crop.